The Relationship between Psychological Safety and Commitment Organizational in Teacher - Watie, Mellynda Sukma; Mulyana, Olievia Prabandini (Universitas Negeri Surabaya, 2023)
This research is based on the importance of teachers to have good psychological security because a teacher who has good psychological security, the teacher will involve himself in the progress of the organization and choose to stay in the organization so that the organizational commitment of the teacher is also good. The population of this study were 32 teachers who taught at the Surabaya Regional Education Foundation. Data collection techniques using organizational commitment scale instruments and psychological safety scales. The results showed a correlation coefficient value of 0.702 (r=0.702) with a significance value of 0.005 (p<0.05) which was analyzed using the Pearson Product Moment correlation test. In this test, it can be seen that there is a positive and significant relationship between psychological safety and organizational commitment in teachers. It is defined that the more positive the level of psychological security possessed by the teacher, the higher the organizational commitment that exists in the teacher. Vice versa, the more negative the level of psychological security owned, the lower the level of organizational commitment owned by the teacher.